Modified micro-etching liquid and method for treating carbon powder in micro-etching liquid in circuit board industry
Through the gradient grafting process and temperature control treatment of forming a polyaniline coating in the micro-etching liquid, the short circuit problem caused by the conductive migration of carbon powder in the PCB black hole process is solved, the efficiency and stability of electrolytic copper extraction is improved, the equipment life is extended, and the reuse rate of the micro-etching liquid is improved.
Patent Information
- Application Number
- CN202510897609.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2045-07-01
AI Technical Summary
In the existing PCB black hole processes, there are problems such as short circuits, accumulation of anode carbon film, insufficient surface modification and poor process stability in the migration of conductive carbon powder, and insufficient reuse of micro-etching liquid, resulting in unstable electrolytic copper extraction process.
Through a gradient grafting process, a 50-100nm polyaniline coating is formed on the surface of the carbon powder in the micro-etching liquid. Combined with impedance feedback control and three-stage temperature control, the micro-etching liquid is treated with a three-stage filtration system to form a modified micro-etching liquid.
The electrolytic efficiency of micro-etching liquid was improved, the copper recovery rate was increased to 92%, the process stability was enhanced, the fluctuation of the toner concentration was controlled within ±5%, the anode maintenance cycle was extended to 1500h, and the reuse rate of micro-etching liquid was increased to 85%.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention provides a modified micro-etching solution and a method for treating carbon powder in a micro-etching solution in the circuit board industry, belonging to the technical field of printed circuit board manufacturing. Background Art
[0002] The black hole plating technology refers to the technology of depositing a layer of high-quality black conductive nano-carbon on the hole wall and using the excellent conductivity of this layer of medium for subsequent electroplating operations, which is also a key process in circuit board manufacturing. The current PCB black hole process generally adopts the following technical solutions: 1. Physical adsorption method: carbon black / graphite particles are directly adsorbed on the hole wall to form a conductive layer; 2. Chemical modification method: surface treatment with silane coupling agent to improve dispersibility; 3. Mechanical filtration method: using cloth bags / filter elements to filter suspended carbon powder.
[0003] The existing PCB black hole process technology has the following defects: 1. Conductive carbon powder migration problem: 0.2 - 0.3 μm carbon powder is driven to migrate directionally by the electric field during electrolysis (mobility > 0.5 cm 2 / (V·s)); 2. Anodic carbon film accumulation: a conductive carbon film is formed on the anode surface (resistivity < 10 3 Ω·m), resulting in short circuit between the anode and the cathode; 3. Insufficient surface modification: traditional modifiers only improve dispersibility and cannot block the conductive path (the surface resistance increase is less than 2 orders of magnitude); 4. Poor process stability: the electrolysis parameters are fixed, resulting in a carbon powder concentration fluctuation > ±30%; 5. The recycling rate of the micro-etching solution is less than 35. Therefore, the present invention provides a treatment method for improving the conductive characteristics of carbon powder in the micro-etching solution of the black hole process through surface modification technology to solve the short circuit problem caused by the conductive migration of carbon powder during the electrolytic copper extraction process. Summary of the Invention
[0004] Based on the above technical defects, the present invention provides a treatment method for improving the conductive characteristics of carbon powder in the micro-etching solution of the black hole process through surface modification technology to solve the short circuit problem caused by the conductive migration of carbon powder during the electrolytic copper extraction process. The present invention forms a 50 - 100 nm polyaniline coating layer on the surface of the carbon powder in the modified micro-etching solution through a gradient grafting process, innovatively adopts impedance feedback control (accuracy ±0.5%) and three-stage temperature control (0 - 25°C), and combines a three-stage filtration system (200 μm → 0.5 μm); after treatment, the surface resistance of the modified micro-etching solution reaches 1.8×10 8 Ω·m, the purity of electrolytic copper is 99.2%, and the recycling rate of the modified micro-etching solution is 85%; the short circuit problem caused by the conductive migration of carbon powder during the electrolytic copper extraction process of the micro-etching solution in the PCB black hole process is solved.
[0005] Technical problems to be solved by the present invention: 1. Cut off the conductive migration path of carbon powder, 2. Eliminate the carbon film accumulation on the anode surface, 3. Improve the stability of the electrolysis process, and 4. Realize the on-line regeneration of the micro-etching solution.
[0006] According to one aspect of the present invention, a method for treating carbon powder in a micro-etching solution in the circuit board industry is provided. The treatment method includes the following steps: Step S1: Treat the micro-etching solution containing carbon powder with a mixed acid solution and ultrasonicate to obtain a pretreated carbon powder micro-etching solution; Step S2: Under an inert atmosphere, mix the pretreated carbon powder micro-etching solution with an activating solution, reflux, centrifuge, and dry to obtain a surface-activated carbon powder micro-etching solution; Step S3: Subject the surface-activated carbon powder micro-etching solution to three-stage gradient polymerization with a mixture containing aniline monomer, ammonium persulfate, and dodecylbenzenesulfonic acid to obtain a modified micro-etching solution.
[0007] Optionally, in step S1, the liquid-solid ratio of the mixed acid solution to the micro-etching solution containing carbon powder is 3:1 to 8:1.
[0008] Optionally, in step S1, the liquid-solid ratio of the mixed acid solution to the micro-etching solution containing carbon powder independently selects any value from 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or the range value between any two of the above.
[0009] Optionally, the mixed acid includes concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1.
[0010] Optionally, the temperature of ultrasonication is 50 to 70 °C, the time of ultrasonication is 20 to 40 min, and the power density of ultrasonication is 80 to 150 W / L.
[0011] Optionally, the temperature of ultrasonication independently selects any value from 50 °C, 55 °C, 60 °C, 65 °C, 70 °C or the range value between any two of the above.
[0012] Optionally, the time of ultrasonication independently selects any value from 20 min, 25 min, 30 min, 35 min, 40 min or the range value between any two of the above.
[0013] Optionally, the power density of ultrasonication is any value from 80 W / L, 90 W / L, 100 W / L, 110 W / L, 120 W / L, 130 W / L, 140 W / L, 150 W / L or the range value between any two of the above.
[0014] Optionally, in step S2, the activating solution includes γ-aminopropyltriethoxysilane, tetraethoxysilane, and ethanol.
[0015] Optionally, the mass percentage of γ-aminopropyltriethoxysilane in the activation solution is 2.0-3.0 wt.%.
[0016] Optionally, the mass percentage of tetraethoxysilane in the activation solution is 0.5-1.0 wt.%.
[0017] Optionally, the solid-liquid ratio of the pretreated toner microetching solution to the activation solution is 1:10-1:15.
[0018] Optionally, in step S2, the inert atmosphere is selected from at least one of nitrogen, argon, and helium.
[0019] Optionally, the reflux temperature is 75-85 °C, and the reflux time is 1.5-2.5 h.
[0020] Optionally, the reflux temperature is independently selected from any value of 75 °C, 76 °C, 78 °C, 80 °C, 82 °C, 85 °C or the range value between any two of the above.
[0021] Optionally, the reflux time is independently selected from any value of 1.5 h, 1.8 h, 2 h, 2.2 h, 2.5 h or the range value between any two of the above.
[0022] Optionally, the drying temperature is 50-80 °C, and the drying time is 4-8 h.
[0023] Optionally, in step S3, the concentration of aniline monomer is 0.3-0.8 mol / L, and the concentration of ammonium persulfate is 0.15-0.4 mol / L.
[0024] Optionally, in step S3, the concentration of aniline monomer is independently selected from any value of 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L or the range value between any two of the above.
[0025] Optionally, the concentration of ammonium persulfate is independently selected from any value of 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L or the range value between any two of the above.
[0026] Optionally, in step S3, the three-stage gradient polymerization includes a pre-oxidation stage, a chain growth stage, and a cross-linking stage.
[0027] Optionally, in step S3, after adding aniline monomer, a pre-oxidation stage is carried out. After adding ammonium persulfate, the temperature is increased for the chain growth stage, and after adding dodecylbenzenesulfonic acid, the temperature is further increased for the cross-linking stage. Among them, the chain growth stage plays a key role in the orderly arrangement of molecular chains. Its absence will lead to a disordered structure of the molecular chains of the modified toner, unable to meet the usage requirements.
[0028] Optionally, the temperature of the pre-oxidation stage is 0~5°C, and the time of the pre-oxidation stage is 30~45 min.
[0029] Optionally, the temperature of the pre-oxidation stage is independently selected from any value of 0°C, 1°C, 2°C, 3°C, 4°C, 5°C or the range value between any two of the above.
[0030] Optionally, the time of the pre-oxidation stage is independently selected from any value of 30 min, 32 min, 35 min, 40 min, 45 min or the range value between any two of the above.
[0031] Optionally, the temperature of the chain growth stage is 15~20°C, and the time of the chain growth stage is 60~120 min.
[0032] Optionally, the temperature of the chain growth stage is independently selected from any value of 15°C, 16°C, 17°C, 18°C, 19°C, 20°C or the range value between any two of the above.
[0033] Optionally, the time of the chain growth stage is independently selected from any value of 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min or the range value between any two of the above.
[0034] Optionally, the temperature of the cross-linking stage is 25~28°C, and the time of the cross-linking stage is 100~150 min.
[0035] Optionally, the temperature of the cross-linking stage is independently selected from any value of 25°C, 26°C, 27°C, 28°C or the range value between any two of the above.
[0036] Optionally, the time of the cross-linking stage is independently selected from any value of 100 min, 110 min, 120 min, 130 min, 140 min, 150 min or the range value between any two of the above.
[0037] Optionally, in step S3, the addition concentration of dodecylbenzenesulfonic acid is 0.08~0.15 mol / L.
[0038] Optionally, in step S3, the addition concentration of dodecylbenzenesulfonic acid is independently selected from any value of 0.08 mol / L, 0.09 mol / L, 0.10 mol / L, 0.11 mol / L, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, 0.15 mol / L or the range value between any two of the above.
[0039] Optionally, during the crosslinking stage, the pH value of the reaction system needs to be controlled at 1.3 - 1.7.
[0040] Optionally, during the crosslinking stage, the pH value of the reaction system is independently selected from any value of 1.3, 1.4, 1.5, 1.6, 1.7 or the range value between any two of the above.
[0041] Optionally, after the crosslinking stage, add NaOH solution to adjust the pH value of the reaction system to 9.0 - 10.5, and the adjustment rate is 0.5 - 1.5 pH / min.
[0042] According to another aspect of the present application, there is provided a modified micro-etching solution prepared by the above treatment method. The thickness of the polyaniline coating layer coated on the surface of the carbon powder in the modified micro-etching solution is 50 - 100 nm.
[0043] Optionally, the porosity of the polyaniline coating layer is 15 - 30%, the average pore diameter of the polyaniline coating layer is 3 - 10 nm, and the specific surface area of the polyaniline coating layer is 50 - 80 m 2 / g.
[0044] Optionally, the surface resistivity of the modified micro-etching solution ≥ 1×10 8 Ω·m, the Zeta potential of the modified micro-etching solution is -35 mV to -40 mV, and the electrolytic mobility of the modified micro-etching solution < 0.05 cm 2 / (V·s).
[0045] Optionally, the dispersion stability of the modified micro-etching solution at a pH value of 1.0 - 2.0 > 48 h.
[0046] As an optional implementation manner, the present invention is realized through the following technical solutions: A method for treating carbon powder in a micro-etching solution in the circuit board industry, comprising the following steps: (a) Pretreating the micro-etching solution containing carbon powder with acid: using a mixed acid system with a volume ratio of H₂SO₄ to HNO₃ of 3:1, and performing ultrasonic treatment for 20 - 40 minutes under the temperature condition of 50 - 70 °C; (b) Surface activation treatment: using an ethanol solution containing γ-aminopropyltriethoxysilane and tetraethoxysilane with a mass concentration of 2.0 - 3.0 wt%, refluxing for 1.5 - 2.5 hours under nitrogen protection at 75 - 85 °C, centrifuging, and drying; (c) In-situ graft polymerization: In a reaction system with an aniline monomer concentration of 0.3 - 0.8 mol / L, an ammonium persulfate concentration of 0.15 - 0.4 mol / L, and a dodecylbenzenesulfonic acid concentration of 0.08 - 0.15 mol / L, controlling the pH value of the reaction system within the range of 1.3 - 1.7, gradient temperature polymerization in three stages is carried out; (d) Dedoping and curing: Add NaOH solution to adjust the pH value of the reaction system to 9.0 - 10.5. By adjusting the pH value, polyaniline is transformed into an insulating state to form a nanoscale coating layer with a thickness of 50 - 100 nm.
[0047] Optionally, in step (a), ultrasonic treatment is carried out using a titanium alloy ultrasonic treatment tank. The frequency range of the ultrasonic treatment tank is 40 ± 5 kHz, and the volume is 300 - 800 L.
[0048] Optionally, in steps (b), (c), and (d), the reaction is carried out in a fluidized bed reactor. The parameters of the fluidized bed reactor are: diameter Φ800 - 1500 mm, and the material is 316L stainless steel or Hastelloy C276.
[0049] Optionally, in step (c), a gradient temperature control system is used in the gradient temperature polymerization. The parameters of the gradient temperature control system are: temperature control accuracy ±0.5 °C, and the temperature adjustment range is -10 °C to 80 °C.
[0050] Optionally, the gradient temperature control system includes a segmented graphite coil heat exchanger, and the independent temperature control accuracy of each temperature zone is ±0.3 °C.
[0051] Optionally, in step (b), after reflux, a vacuum drying unit is used for drying. The parameters of the vacuum drying unit are: working pressure ≤50 Pa, and it is equipped with a microwave-assisted heating device (frequency 2450 ± 50 MHz).
[0052] Optionally, the vacuum drying unit is equipped with an on-line moisture monitor with a detection accuracy of ±0.1% moisture content.
[0053] Optionally, the surface resistivity of the modified micro-etching solution ≥1×10 8 Ω·m (measured according to ASTM D257 standard), the Zeta potential is stabilized at -35 mV to -40 mV (measured at pH = 1.5), and the electrolytic mobility < 0.05 cm 2 / (V·s) (tested under an electric field strength of 0.5 A / dm 2 ).
[0054] Optionally, the dispersion stability of the modified micro-etching solution in an environment with pH = 1.0 - 2.0 is > 48 hours (particle size change rate < 5%).
[0055] Optionally, the modified micro-etching solution is applied to a pulsed electrolytic copper extraction device (reverse cycle: 25 - 35 s forward / 3 - 8 s reverse), with a three-stage gradient filtration module (200 μm metal filter screen → 1 μm ceramic membrane → 0.5 μm electrophoresis filter element).
[0056] Optionally, the modified micro-etching solution is applied to a pulsed electrolysis device equipped with: an iridium-plated titanium anode plate (iridium content 15 - 20 wt%); a 316L stainless steel cathode plate; an on-line impedance monitoring module (detection frequency 1 kHz - 100 kHz).
[0057] Optionally, when the modified micro-etching solution is applied, a hydrocyclone electrophoresis pretreatment unit is also set up, and the technical parameters include: electric field strength 500 - 1000 V / m; centrifugal factor 80 - 150 G; treatment flow rate 5 - 15 m 3 / h.
[0058] The beneficial effects that the present invention can produce include: 1) Through the gradient grafting process, a 50 - 100 nm polyaniline coating layer is formed on the surface of the carbon powder in the modified micro-etching solution. The present invention innovatively adopts impedance feedback control (accuracy ±0.5%) and three-stage temperature control (0 - 25 °C), combined with a three-stage filtration system (200 μm → 0.5 μm). Through the three-stage temperature control, the micro-etching solution containing carbon powder can be modified through a pre-oxidation stage, a chain growth stage, and a cross-linking stage, enabling the molecular chains in the modified micro-etching solution to grow orderly; the electrolysis efficiency of the treated modified micro-etching solution is improved, and its copper recovery rate is increased from 78% to 92% (Cu 2+ 40 g / L working condition), the purity of electrolytic copper is 99.2%, solving the short-circuit problem caused by the conductive migration of carbon powder during the electrolytic copper extraction process; the process stability of the modified micro-etching solution is enhanced, and the carbon powder concentration fluctuation is controlled within ±5%; the use of the modified micro-etching solution can extend the equipment life, and its anode maintenance period can be extended from 200 h to 1500 h; the reuse rate of the modified micro-etching solution prepared by the present invention is increased to 85%, which can significantly improve the environmental protection benefits.
[0059] 2) The surface resistivity of the modified micro-etching solution prepared by the method for treating carbon powder in the micro-etching solution in the circuit board industry provided by the present invention is 1.8×10 8 Ω·m, compared with the surface resistivity of 2.5×10 5 Ω·m of the micro-etching solution prepared by the traditional process, which is increased by 719 times; the copper recovery rate of the modified micro-etching solution during the electrolytic copper extraction process is 92%, compared with the copper recovery rate of 78% of the micro-etching solution prepared by the traditional process, which is increased by 18%; the maintenance period of the modified micro-etching solution is 1500 h, compared with the maintenance period of 200 h of the micro-etching solution prepared by the traditional process, which is increased by 650%; the reuse rate of the modified micro-etching solution is 85%, compared with the reuse rate of 30% of the micro-etching solution prepared by the traditional process, which is increased by 183%. Detailed implementation manners
[0060] The present application will be described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0061] Unless otherwise specified, the raw materials in the embodiments of the present application are all purchased through commercial channels.
[0062] Embodiment 1 Experimental materials: Micro-etching solution containing carbon powder: taken from the waste liquid of the black hole process in a PCB factory, D 50 = 0.25 μm, specific surface area 85 m 2 / g.
[0063] Chemical reagents: Mixed acid system: concentrated sulfuric acid (98%) and concentrated nitric acid (65%) are prepared according to a volume ratio of 3:1; aniline monomer: Aladdin reagent, purity ≥ 99.5%, purified by vacuum distillation; SDBS (sodium dodecylbenzenesulfonate): Kemiou Chemical, analytical pure.
[0064] Main equipment: Ultrasonic processor: Sonics VCX750 (adjustable from 20 - 40 kHz); polymerization reactor: 500 mL jacketed glass reactor (including mechanical stirring); freeze dryer: Labconco FreeZone 4.5L.
[0065] [[ID=3,1]]Process implementation steps Step 1: Acid pretreatment of the micro-etching solution containing carbon powder 1. Take 200 g of the micro-etching solution containing carbon powder and add it to the mixed acid solution (H2SO4:HNO3 = 3:1 v / v), with a liquid-solid ratio of 5:1; 2. Start ultrasonic treatment (4 kHz, power density 100 W / L) and treat at 60 °C for 30 minutes to uniformly mix the micro-etching solution containing carbon powder with the mixed acid solution; 3. Use the polymerization reactor to treat at a constant temperature of 60 °C for 30 minutes; 4. After vacuum filtration, wash with deionized water until neutral. After the conductivity of the pretreated carbon powder micro-etching solution < 5 μS / cm, perform surface activation treatment.
[0066] Step 2: Surface activation treatment 1. Prepare the activation solution: APTES (γ-aminopropyltriethoxysilane) 2.5 wt%; TEOS (tetraethoxysilane) 0.8 wt%; ethanol / water = 95 / 5 (v / v); 2. Mix the pretreated toner microetching solution and the activation solution at a solid-liquid ratio of 1:10; 3. After refluxing at 80 °C for 2 hours under nitrogen protection; 4. After centrifugal separation and vacuum drying at 60 °C for 6 h, a surface-activated toner microetching solution is obtained.
[0067] Step 3: In-situ graft polymerization Prepare an aniline monomer with a concentration of 0.5 mol / L and pre-cool it to 0 °C for standby; add the surface-activated toner microetching solution and carry out pre-oxidation at 0 °C. After reacting for 30 min under stirring at 300 rpm, slowly add ammonium persulfate with a concentration of 0.25 mol / L into the aniline monomer at a rate of 1 mL / min, raise the temperature to 15 °C, and react for 90 min under stirring at 500 rpm; then add sodium dodecylbenzenesulfonate SDBS with a concentration of 0.12 mol / L, control the pH value of the reaction to be 1.5, raise the temperature to 25 °C again, and react for 120 min under stirring at 200 rpm until the reaction ends. Add NaOH solution to adjust the pH value of the system to 9.5 at a rate of 0.5 pH / min. After the reaction ends, centrifuge to collect the product to obtain a modified microetching solution. The nano-scale coating layer on the surface of the carbon powder in the microetching solution is 80 nm, the porosity of the polyaniline coating layer is 20%, the average pore diameter is 8 nm, and the specific surface area is 60 m 2 / g; Step 4: Post-treatment and characterization 1. After freeze-drying the modified microetching solution under the conditions of vacuum freeze-drying (-50 °C, 10 Pa, 24 h), perform particle size analysis and electrochemical performance testing. The specific testing equipment and conditions are as follows: 2. Particle size analysis: Mastersizer 3000 laser particle size analyzer; 3. Electrochemical testing: PARSTAT 4000 electrochemical workstation.
[0068] The specific experimental results after testing are shown in Table 1 below.
[0069] Table 1: Comparison of performance parameters of the microetching solution before and after modification
[0070] As can be seen from Table 1, the surface resistivity of the modified microetching solution is 1.8×10 8 Ω·m; the copper recovery rate of the modified microetching solution in the process of electrolytic copper extraction is 92%, which is 14% higher than the copper recovery rate of 78% of the microetching solution before modification; the aggregation index of the modified microetching solution is 1.12, and the Zeta (pH = 1.5) of the modified microetching solution is -38 mV. Compared with -25 mV of the microetching solution before modification, the greater the absolute value of the Zeta potential, the stronger the electrostatic repulsion force between particles, and the more stable the dispersion system.
[0071] Example 2 Experimental materials: Micro-etching solution containing carbon powder: Waste liquid from the black hole process of a PCB factory, D 50 = 0.25 μm, specific surface area 85 m 2 / g.
[0072] Chemical reagents: Mixed acid system: Concentrated sulfuric acid (98%) and concentrated nitric acid (65%) are prepared according to a volume ratio of 3:1; Aniline monomer: Aladdin reagent, purity ≥ 99.5%, purified by vacuum distillation; SDBS (sodium dodecylbenzenesulfonate): Kemiou Chemical, analytical pure.
[0073] Main equipment: Ultrasonic processor: Sonics VCX750 (adjustable from 20 - 40 kHz); Polymerization reactor: 500 mL jacketed glass reactor (with mechanical stirring); Freeze dryer: Labconco FreeZone 4.5L.
[0074] Process implementation steps Step 1: Acid pretreatment of the micro-etching solution containing carbon powder 1. Take 200 g of the micro-etching solution containing carbon powder and add it to the mixed acid solution (H2SO4:HNO3 = 3:1 v / v), with a liquid-solid ratio of 3:1; 2. Start ultrasonic treatment (40 kHz, power density 80 W / L) and treat at 70 °C for 20 minutes to uniformly mix the micro-etching solution containing carbon powder with the mixed acid solution; 3. Use the polymerization reactor to treat at a constant temperature of 50 °C for 40 minutes; 4. After vacuum filtration, wash with deionized water until neutral. After the conductivity of the pretreated carbon powder micro-etching solution < 5 μS / cm, perform surface activation treatment.
[0075] Step 2: Surface activation treatment 1. Prepare the activation solution: APTES (γ-aminopropyltriethoxysilane) 2.0 wt%; TEOS (tetraethoxysilane) 0.5 wt%; Ethanol / water = 95 / 5 (v / v); 2. Mix the pretreated carbon powder micro-etching solution with the activation solution at a solid-liquid ratio of 1:12; 3. After refluxing at 75 °C for 2.5 hours under argon protection; 4. After centrifugal separation and vacuum drying at 50 °C for 8 h, obtain the surface-activated carbon powder micro-etching solution.
[0076] Step 3: In-situ graft polymerization Prepare an aniline monomer with a concentration of 0.3 mol / L and pre-cool it to 0 °C for standby; add a surface-activated carbon powder microetching solution and perform pre-oxidation at 2 °C. After reacting for 40 min under stirring at 300 rpm, slowly add ammonium persulfate with a concentration of 0.15 mol / L to the aniline monomer at a rate of 1 mL / min, raise the temperature to 18 °C, and react for 120 min under stirring at 500 rpm; then add sodium dodecylbenzenesulfonate SDBS with a concentration of 0.08 mol / L, control the pH value of the reaction to 1.3, raise the temperature to 26 °C again, and react for 150 min under stirring at 200 rpm until the reaction ends. Add NaOH solution to adjust the pH value of the system to 9.0 at a rate of 1.0 pH / min. After the reaction ends, centrifuge to collect the product to obtain a modified microetching solution. The nano-scale coating layer on the surface of the carbon powder in the microetching solution is 50 nm, the porosity of the polyaniline coating layer is 15%, the average pore diameter is 3 nm, and the specific surface area is 50 m 2 / g; Step 4: Post-treatment and characterization 1. Freeze-dry the modified microetching solution under the conditions of vacuum freeze-drying (-50 °C, 10 Pa, 24 h), and then perform particle size analysis and electrochemical performance testing. The specific testing equipment and conditions are as follows: 2. Particle size analysis: Mastersizer 3000 laser particle size analyzer; 3. Electrochemical testing: PARSTAT 4000 electrochemical workstation.
[0077] The specific experimental results after testing are shown in Table 2 below.
[0078] Table 2: Comparison of performance parameters of the microetching solution before and after modification
[0079] As can be seen from Table 2, the surface resistivity of the modified microetching solution is 1.7×10 8 Ω·m; the copper recovery rate of the modified microetching solution in the electrolytic copper extraction process is 90%, which is 12% higher than the copper recovery rate of 78% of the microetching solution before modification; the aggregation index of the modified microetching solution is 1.10, and the Zeta (pH = 1.5) of the modified microetching solution is -35 mV. Compared with -25 mV of the microetching solution before modification, the greater the absolute value of the Zeta potential, the stronger the electrostatic repulsion force between particles, and the more stable the dispersion system.
[0080] Example 3 Experimental materials: Microetching solution containing carbon powder: taken from the black hole process waste liquid of a PCB factory, D 50 = 0.25 μm, specific surface area 85 m 2 / g.
[0081] Chemical reagents: Mixed acid system: concentrated sulfuric acid (98%) and concentrated nitric acid (65%) are prepared according to a volume ratio of 3:1; aniline monomer: Aladdin reagent, purity ≥99.5%, purified by vacuum distillation; SDBS (sodium dodecylbenzenesulfonate): Kemiou Chemical, analytical pure.
[0082] Main equipment: Ultrasonic processor: Sonics VCX750 (adjustable from 20 - 40 kHz); polymerization reactor: 500 mL jacketed glass reactor (with mechanical stirring); freeze dryer: Labconco FreeZone 4.5L.
[0083] Process implementation steps Step 1: Acid pretreatment of the micro - etching solution containing carbon powder 1. Take 200 g of the micro - etching solution containing carbon powder and add it to the mixed acid solution (H2SO4:HNO3 = 3:1 v / v), with a liquid - to - solid ratio of 8:1; 2. Turn on the ultrasonic treatment (40 kHz, power density 150 W / L) and treat at 50 °C for 40 minutes to uniformly mix the micro - etching solution containing carbon powder and the mixed acid solution; 3. Use the polymerization reactor to treat at a constant temperature of 70 °C for 20 minutes; 4. After vacuum filtration, wash with deionized water until neutral. After the conductivity of the pretreated carbon powder micro - etching solution < 5 μS / cm, perform surface activation treatment.
[0084] Step 2: Surface activation treatment 1. Prepare the activation solution: APTES (γ - aminopropyltriethoxysilane) 3.0 wt%; TEOS (tetraethoxysilane) 1.0 wt%; ethanol / water = 95 / 5 (v / v); 2. Mix the pretreated carbon powder micro - etching solution and the activation solution according to a solid - to - liquid ratio of 1:15; 3. Under argon protection, reflux at 85 °C for 1.5 hours; 4. After centrifugal separation, vacuum dry at 80 °C for 4 h to obtain the surface - activated carbon powder micro - etching solution.
[0085] Step 3: In - situ graft polymerization Prepare aniline monomer with a concentration of 0.8 mol / L and pre-cool it to 5 °C for standby; add the surface-activated carbon powder micro-etching solution and perform pre-oxidation at 5 °C. After reacting for 45 min under stirring at 300 rpm, slowly add ammonium persulfate with a concentration of 0.4 mol / L to the aniline monomer at a rate of 1 mL / min, raise the temperature to 20 °C, and react for 120 min under stirring at 500 rpm; then add sodium dodecylbenzenesulfonate SDBS with a concentration of 0.15 mol / L, control the pH value of the reaction to 1.7, raise the temperature to 28 °C again, and react for 100 min under stirring at 200 rpm until the reaction ends. Add NaOH solution to adjust the pH value of the system to 10.5 at a rate of 1.5 pH / min. After the reaction ends, centrifuge to collect the product to obtain the modified micro-etching solution. The nano-scale coating layer on the surface of the carbon powder in the micro-etching solution is 100 nm, the porosity of the polyaniline coating layer is 30%, the average pore diameter is 10 nm, and the specific surface area is 80 m 2 / g; Step 4: Post-treatment and Characterization 1. After freeze-drying the modified micro-etching solution under the conditions of vacuum freeze-drying (-50 °C, 10 Pa, 24 h), perform particle size analysis and electrochemical performance testing. The specific testing equipment and conditions are as follows: 2. Particle size analysis: Mastersizer 3000 laser particle size analyzer; 3. Electrochemical testing: PARSTAT 4000 electrochemical workstation.
[0086] The specific experimental results after testing are shown in Table 3 below.
[0087] Table 3: Comparison of performance parameters of the micro-etching solution before and after modification
[0088] As can be seen from Table 3, the surface resistivity of the modified micro-etching solution is 1.9×10 8 Ω·m; the copper recovery rate of the modified micro-etching solution in the electrolytic copper extraction process is 93%, which is 15% higher than the copper recovery rate of 78% of the micro-etching solution before modification; the aggregation index of the modified micro-etching solution is 1.10, and the Zeta (pH = 1.5) of the modified micro-etching solution is -39 mV. Compared with -25 mV of the micro-etching solution before modification, the larger the absolute value of the Zeta potential, the stronger the electrostatic repulsion force between particles, and the more stable the dispersion system.
[0089] Example 4 (Industrial mass production system) (1) Equipment configuration and process control, core equipment list: Continuous ultrasonic treatment system: processing capacity 500 kg / h; Titanium alloy tank: 40kHz dual-frequency ultrasonic wave, power density 80 - 120W / L; Fluidized bed polymerization reactor: Made of Hastelloy C276, Φ1200×3000mm, equipped with a high-precision temperature control system (±0.2℃); Intelligent centrifugal separation system, horizontal spiral centrifuge, G value 3000G, carbon powder recovery rate ≥99.5%; Vacuum belt dryer: Processing capacity 500kg / h, working vacuum degree ≤10Pa, microwave-assisted heating (2450MHz, power adjustable).
[0090] (2) Key points of mass production process control Table 4: Process parameter monitoring system
[0091] (3) Deepened comparative experiment data table: Table 5: Temperature gradient scheme design (fixing other parameters)
[0092] Using the process parameter monitoring system in Table 4, according to the temperature gradient scheme shown in Table 5, modify the micro-etching solution containing carbon powder to prepare a modified micro-etching solution. The specific modified micro-etching solutions prepared are shown in Table 6 and Table 7 below.
[0093] Table 6: Influence of temperature gradient on the coating layer performance of carbon powder in the modified micro-etching solution
[0094] It can be seen from Table 6 that the test group in Group A was subjected to gradient heating according to the temperature range of the stage gradient. The coating thickness in Group A was within the coating layer of 50 - 100nm level, with small thickness deviation, and the surface resistivity, electrolytic migration rate and bonding strength of the modified micro-etching solution all met the requirements; the gradient heating in the other three groups was not within the range of the stage gradient heating, and the coating thickness, thickness deviation of the carbon powder in the prepared modified micro-etching solution, and the electrolytic migration rate and bonding strength of the modified micro-etching solution could not meet the requirements.
[0095] Table 7: Relationship between temperature gradient and coating thickness
[0096] In Table 7, note: In the compression type Group D, Stage II is cancelled, directly from Stage I to Stage III.
[0097] As can be seen from Table 7, in the stepped three-stage heating Group A, the thickness of the polyaniline coating on the surface of the carbon powder in the modified microetchant is 85 nm, and the crystallinity is 78.5%, meeting the requirements; in the high-temperature Group B, the coating thickness is relatively low and cannot meet the requirements; the temperatures in the low-temperature Group C are all lower than those in the three stages of Group A, and its coating thickness meets the requirements, having a relatively small impact on the coating thickness compared to the high-temperature Group B; the compression Group D did not undergo the chain growth stage in the second stage and directly entered the crosslinking stage in the third stage. Its coating thickness is relatively thick and the crystallinity is high, unable to meet the usage requirements; when the temperature is too high, the chain growth is relatively fast and the coating thickness is too thick, so it cannot meet the requirements.
[0098] Taking the temperature gradient of the optimal temperature gradient Group A as the specific operating conditions, five parallel experiments were carried out on the microetchant containing carbon powder. The specific experimental results are shown in Table 8 below.
[0099] Table 8: Verification experiment of the optimal temperature gradient (n = 5)
[0100] As can be seen from Table 8, within the optimal temperature gradient range, the thickness of the polyaniline coating layer on the surface of the carbon powder in the modified microetchant, as well as various indicators such as the resistivity, mobility, and copper recovery rate of the modified microetchant, all meet the requirements, and the values of the five parallel experiments are basically the same.
[0101] Through the above experiments, it was found that the stepped temperature control (Group A) achieved the best balance between thickness uniformity (±14.1%) and electrical properties; although the compression type scheme (Group D) obtained the maximum thickness, the thickness deviation increased by 33.3% and the bonding strength decreased; for every 5 °C increase in the temperature gradient, the polymerization rate increased by 120% but the crystallinity decreased by 8 - 12%; Stage II (15 - 20 °C) plays a key role in the orderly arrangement of molecular chains, and its absence will lead to a disordered structure (Group D).
[0102] To sum up, in order to ensure the quality of the modified microetchant, the present invention takes the following quality guarantee measures for the modified microetchant: 1. Sampling each batch for detecting the integrity of the coating layer on the surface of the carbon powder in the modified microetchant: Observation: The acceleration voltage is 5 kV, observing more than 50 particles. The qualified standard for the coating thickness: 50 - 100 nm (allowing a deviation of ±1 at 5%); 2. Process abnormal warning mechanism: Trigger automatic shutdown when the impedance mutation > 5%, and start emergency cooling when the temperature fluctuation > ±1 °C; 3. Product grading standard: AA grade: Coating integrity ≥ 95%, resistivity ≥ 1 × 10 8 Ω·m; A grade: Coating integrity ≥ 90%, resistivity ≥ 5 × 10 7Ω·m; Grade B: Coating integrity ≥ 85%, resistivity ≥ 1×10 7 Ω·m; Only the modified micro-etching solution that has passed quality assurance can be used.
[0103] Comparative example: Compare the modified micro-etching solution prepared by the present invention with the traditional silane-modified micro-etching solution process. The specific content is shown in Tables 9 - 11 below.
[0104] Table 9: Comparison of the modified micro-etching solution process with the traditional silane-modified micro-etching solution process
[0105] As can be seen from Table 9, for the modified micro-etching solution, its surface resistivity is 1.8×10 8 Ω·m, which is 719 times higher than the surface resistivity of 2.5×10 5 Ω·m of the micro-etching solution prepared by the traditional process; the copper purity of the modified micro-etching solution during the electrolytic copper extraction process is 99.2%, which is 2.4% higher than the copper purity of 96.8% of the micro-etching solution prepared by the traditional process; the anode maintenance period of the modified micro-etching solution is 1500h, which is 650% higher than the maintenance period of 200h of the modified micro-etching solution prepared by the traditional process; the electrolytic migration rate of the modified micro-etching solution is 0.03cm 2 / (V·s), which is 94% lower than the reuse rate of 0.51cm 2 / (V·s) of the micro-etching solution prepared by the traditional process.
[0106] Table 10: Comparison of core performance of the modified micro-etching solution with the traditional silane modification process (laboratory scale)
[0107] As can be seen from Table 10, for the modified micro-etching solution, its surface resistivity is 1.8×10 8 Ω·m, which is 719 times higher than the surface resistivity of 2.5×10 5 Ω·m of the modified micro-etching solution prepared by the traditional process; the electrolytic migration rate is 0.03cm 2 / (V·s), which is 94.1% higher than 0.51cm 2 / (V·s) of the modified micro-etching solution of the traditional process; after electrolytic copper extraction of the modified micro-etching solution, the copper recovery increased by 18.2%, the carbon powder sedimentation rate increased by 82.2%, and the anodic polarization resistance increased by 646%; the solution conductivity increased by 646%, and the conductivity of the solution increased by 86.2%, all of which meet the requirements.
[0108] The specific content is shown in Tables 9 - 11 below. Table 11: Process stability comparison (production data for 3 consecutive months)
[0109] As can be seen from Table 11, after the electrolytic copper extraction process of the modified microetchant, the purity of the electrolytic copper increased by 6.2 times, the fluctuation of the carbon powder concentration increased by 9.8 times, the fluctuation of the anode voltage increased by 8 times, the fluctuation of the current efficiency increased by 9.4 times, and the fluctuation of the energy consumption increased by 8.6 times, all of which can meet the requirements.
[0110] A dispersion stability experiment was carried out on the modified microetchant of the present invention and the modified microetchant prepared by the traditional process in an environment with a pH value of 1.0 - 2.0 for 48 hours. The specific test results are shown in Table 12.
[0111] Table 12: Comparison of electrolytic mobility at different pH values
[0112] In Table 12: within the range of pH = 1.0 - 2.0, the fluctuation range of the mobility of the modified microetchant of the present invention within 48 hours is ±0.005, and the fluctuation of the modified microetchant prepared by the traditional process within 48 hours is ±0.15, which is larger than the fluctuation range of the modified microetchant of the present invention and is unstable. Therefore, the dispersion stability of the modified microetchant of the present invention in an environment with a pH value of 1.0 - 2.0 > 48 hours.
[0113] In summary, the electrolysis efficiency of the modified microetchant prepared by the method for treating carbon powder in the microetchant for the circuit board industry provided by the present invention is improved. The copper recovery rate of the electrolytic copper extraction treatment on it is increased from 78% to 92% (Cu 2+ 40 g / L working condition); the process stability of the modified microetchant is enhanced, and the fluctuation of the carbon powder concentration in it is controlled within ±5%; the use of the modified microetchant can extend the service life of the equipment, and the anode maintenance period can be extended from 200 hours to 1500 hours; the reuse rate of the modified microetchant prepared by the present invention can be increased to 85%, which can significantly improve the environmental protection benefit and is particularly suitable for solving the short-circuit problem caused by the conductive migration of carbon powder during the copper extraction process.
[0114] The above are only several embodiments of the present application, and do not impose any form of limitation on the present application. Although the present application is disclosed above with preferred embodiments, it is not intended to limit the present application. Any person skilled in the art, without departing from the technical solution of the present application, makes some changes or modifications using the disclosed technical content, which are equivalent to equivalent implementation cases and all fall within the scope of the technical solution.
Claims
1. A method for treating carbon powder in a micro-etching solution in the circuit board industry, characterized in that, The processing method includes the following steps: Step S1: Treat the micro-etching solution containing carbon powder with a mixed acid solution and perform ultrasonic treatment to obtain a pretreated carbon powder micro-etching solution; Step S2: Under an inert atmosphere, mix the pretreated carbon powder micro-etching solution with an activating solution, reflux, centrifuge, and dry to obtain a surface-activated carbon powder micro-etching solution; Step S3: Subject the surface-activated carbon powder micro-etching solution to three-stage gradient polymerization through a mixture containing aniline monomer, ammonium persulfate, and dodecylbenzenesulfonic acid to obtain a modified micro-etching solution.
2. The processing method according to claim 1, wherein In step S1, the liquid-solid ratio of the mixed acid solution to the micro-etching solution containing carbon powder is 3:1 to 8:1; The mixed acid solution includes concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; The temperature of the ultrasonic treatment is 50 to 70 °C, the time of the ultrasonic treatment is 20 to 40 min, and the power density of the ultrasonic treatment is 80 to 150 W / L.
3. The processing method according to claim 1, characterized in that In step S2, the activating solution includes γ-aminopropyltriethoxysilane, tetraethoxysilane, and ethanol; The mass percentage of γ-aminopropyltriethoxysilane in the activating solution is 2.0 to 3.0 wt.%; The mass percentage of tetraethoxysilane in the activating solution is 0.5 to 1.0 wt.%; The solid-liquid ratio of the pretreated carbon powder micro-etching solution to the activating solution is 1:10 to 1:
15.
4. The processing method according to claim 1, characterized in that In step S2, the inert atmosphere is selected from at least one of nitrogen, argon, and helium; The temperature of the reflux is 75 to 85 °C, and the time of the reflux is 1.5 to 2.5 h; The temperature of the drying is 50 to 80 °C, and the time of the drying is 4 to 8 h.
5. The processing method according to claim 1, characterized in that, In step S3, the concentration of the aniline monomer is 0.3 to 0.8 mol / L, and the concentration of the ammonium persulfate is 0.15 to 0.4 mol / L.
6. The processing method according to claim 1, wherein In step S3, the three-stage gradient polymerization includes a pre-oxidation stage, a chain growth stage, and a cross-linking stage; The temperature of the pre-oxidation stage is 0 to 5 °C, and the time of the pre-oxidation stage is 30 to 45 min; The temperature of the chain growth stage is 15 to 20 °C, and the time of the chain growth stage is 60 to 120 min; The temperature of the cross-linking stage is 25 to 28 °C, and the time of the cross-linking stage is 100 to 150 min.
7. The processing method according to claim 6, wherein In step S3, the added concentration of the dodecylbenzenesulfonic acid is 0.08 to 0.15 mol / L; During the cross-linking stage, the pH value of the reaction system needs to be controlled at 1.3 to 1.7; After the cross-linking stage, add a NaOH solution to adjust the pH value of the reaction system to 9.0 to 10.5, and the adjustment rate is 0.5 to 1.5 pH / min.
8. A modified microetching solution prepared by the treatment method according to any one of claims 1 to 7, characterized in that, The thickness of the polyaniline coating layer coated on the surface of the carbon powder in the modified micro-etching solution is 50 to 100 nm; The porosity of the polyaniline coating layer is 15-30%, the average pore size of the polyaniline coating layer is 3-10 nm, and the specific surface area of the polyaniline coating layer is 50-80 m 2 / g.
9. The modified microetching solution according to claim 8, wherein, The surface resistivity of the modified micro-etching solution ≥ 1×10 8 Ω·m, the Zeta potential of the modified micro-etching solution is -35 mV to -40 mV, and the electrolytic mobility of the modified micro-etching solution < 0.05 cm 2 / (V·s).
10. The modified microetching solution according to claim 8, wherein, The dispersion stability of the modified micro-etching solution at a pH value of 1.0 to 2.0 is > 48 h.
Citation Information
Patent Citations
Technology for regenerating and cycling circuit board microetching waste liquid
CN101608337A
Resource recovery method of sodium persulfate-sulfuric acid serial copper-containing microetch waste liquor for PCB (Printed Circuit Board)
CN103435092A
Circuit board micro-etching coarsening liquid cyclic regeneration additive and application thereof
CN114875409A
Micro-etching liquid on-line electrolysis copper extraction cyclic regeneration process
CN115449849A
Micro-etching coarsening liquid for circuit board and preparation method of micro-etching coarsening liquid
CN119491225A